Effects of detraining in age-group swimmers performance, energetics and kinematics. Issue 13 (3rd July 2019) - Zacca, Rodrigo; Toubekis, Argyris; Freitas, Laura; Silva, Ana Filipa; Azevedo, Rui; Vilas-Boas, João Paulo; Pyne, David B.; Castro, Flávio A. De S.; Fernandes, Ricardo J.
ABSTRACT: Changes in performance, energetics and kinematics during age-group swimmers off-season inform the prescription of training for the following season. Age-group swimmers (n = 15, age 14.3 ± 0.7 years) of equal maturational stage performed a 400-m front crawl (T400) before and after a four-weeks training cessation period. Performance-related energetic and kinematic variables were obtained controlling for anthropometric changes and non-swimming specific physical activities during off-season. T400 time decreased 3.8% (95%CI 1.4 to 6.1%; p < 0.01; d = 0.90) with non-specific physical activities (1814 ± 1989 MET-min·wk −1 ) accounting for 40% of the underlying variance (p = 0.01; η 2 = 0.40). Stroke rate and stroke index decreased despite similar stroke length and index of coordination values. Although mean response time, amplitude, maximal oxygen uptake, heart rate, total energy expenditure, metabolic power and energy cost were similar, aerobic contribution decreased by 1.8% (−2.7 to −0.9%; p < 0.01; d = −1.19) and anaerobic lactic contribution increased by 1.6% (0.8 to 2.5%; p < 0.01; d = 1.08) over the off-season. Impaired performance was mainly associated with a decreased stroke rate (r = −0.85 to −0.61; p ≤ 0.02), increased peak blood lactate (r = −0.52; p = 0.05) and fewer non-swimming specific physical activities performed during the off-season (r = −0.58; p = 0.03). The end-of-season cessation of training yielded moderate impairments in age-group swimmers performance-related energetic and kinematic factors, however non-specific physical activities can minimise fitness losses.